A Histopathological Study of Direct Pulp Capping with Adhesive Resins - M. Ghavamnasiri; F. Maleknejad; J. Salhenejad; H. Moosavi (Frontiers in Dentistry, 2004)
Statement of Problem: Recently, it has been proposed that different adhesive materials can be used for direct pulp capping. Previous studies have demonstrated that multi steps dentin adhesives could form reparative dentin similar to calcium hydroxide (CH). Purpose: The aim of this study was to evaluate the histological pulp response of ninety mechanically exposed cat pulps to two adhesive resins (Scotch Bond MP and Single Bond 3M) were compared with a calcium hydroxide cement (Dycal, Dentsply). Materials and Methods: Class V facial cavities with similar pulpal exposures were prepared in canines. In the experimental groups phosphoric acid was used to etch the enamel and dentin and pulp exposure, and after it dentin adhesives was applied. The exposure point of the control group was capped with Dycal then the remainder of the cavities was etched and a dentin adhesive (single bond) was applied. All of the cavities were restored with a composite resin (Z 100) in usual manner. The animals were scarified after 7, 30 and 60 days (n=30), and the pulp evaluated histologically, statistical analysis was carried out with Kruskal- Wallis test (α=0.05). Results: The data showed that most of the cases had mild inflammation of pulp tissue. There was no significant difference in inflammatory reaction of pulp by Dycal and two adhesive systems, severe inflammatory reaction of pulp was observed only in most of the 30- day Single Bond group. Soft tissue organization of dentin bridge was less than Scotch Bond and Dycal groups, the differentiation of dentin bridge was less than Scotch Bond group after 7 days. Conclusion: Slight inflammatory cell infiltration was the main reaction of exposed pulp when two commercially available adhesive resins were placed directly on the exposed pulp. There was no significant difference in inflammatory reaction of pulp between Dycal and two adhesive systems after 7 days and 60 days. After 7 days most of the specimens showed an amount of predentin deposition.